2008
DOI: 10.1080/14786430802438200
|View full text |Cite
|
Sign up to set email alerts
|

Ab-initiotheory of temperature-dependent magneto-resistivities

Abstract: We present the first ab-initio type descriptions of the temperature dependence of the magnetic part of the electrical conductivity. We implemented the Disordered Local Moment (DLM) scheme into Kubo's linear-response formalism using the screened Korringa-Kohn-Rostoker (KKR) approach. In order to test the proposed scheme, we calculated the magnetic resistivity of bulk Fe and Co. The results seem to give a qualitatively correct temperature dependence of the magnetic part of the electrical resistivity in the ferro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…The resistivity is 85 µΩ cm, which agrees well both with supercell LB calculations 14 and with experiment, while the value obtained in Ref. 35 is almost twice larger. The origin of this disagreement is unclear.…”
Section: B Disordered Local Moment (Dlm) Modelsupporting
confidence: 79%
See 2 more Smart Citations
“…The resistivity is 85 µΩ cm, which agrees well both with supercell LB calculations 14 and with experiment, while the value obtained in Ref. 35 is almost twice larger. The origin of this disagreement is unclear.…”
Section: B Disordered Local Moment (Dlm) Modelsupporting
confidence: 79%
“…The first implementation of the DLM method for resistivity studies was done in Ref. 35. Our implementation of the linear response technique within the TB-LMTO-CPA method including disorder-induced vertex corrections is described in Refs.…”
Section: B Disordered Local Moment (Dlm) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Buruzs et al 34 calculated the SDR for Fe and Co using the DLM approach within the Korringa-KohnRostocker method and found that their method significantly overestimates the paramagnetic SDR in these metals. The source of disagreement with our supercell method for Fe is unknown to us.…”
Section: A Paramagnetic Statementioning
confidence: 99%
“…15 the SDR was calculated using a hybrid method, in which the electronic structure is described by DLM, and the SDR is calculated in a multilayer geometry as an extrapolation from large values of the imaginary part of energy (1 and 2 mRy) without including vertex corrections. The resulting SDR of Fe and Co was strongly overestimated.…”
mentioning
confidence: 99%